Genetic variation of HvXYN1 associated with endoxylanase activity and TAX content in barley (Hordeum vulgare L.) - Lu, Xueli (BMC Plant Biol, 2019)
BACKGROUND: Endo-β-1,4-xylanase1 (EA), the key endoxylanase in plants, is involved in the degradation of arabinoxylan during grain germination. In barley (Hordeum vulgare L.), one gene (HvXYN-1) that encode a endo-beta-1,4-xylanase, has been cloned. However, the single nucleotide polymorphisms (SNPs) that affect the endoxylanase activity and total arabinoxylan (TAX) content have yet to be characterized. The investigation of genetic variation in HvXYN1 may facilitate a better understanding of the relationship between TAX content and EA activity in barley. RESULTS: In the current study, 56 polymorphisms were detected in HvXYN1 among 210 barley accessions collected from 34 countries, with 10 distinct haplotypes identified. The SNPs at positions 110, 305, 1045, 1417, 1504, 1597, 1880 bp in the genomic region of HvXYN1 were significantly associated with EA activity (P < 0.0001), and the sites 110, 305, and 1045 were highly significantly associated with TAX content. The amount of phenotypic variation in a given trait explained by each associated polymorphism ranged from 6.96 to 9.85%. Most notably, we found two variants at positions 1504 bp and 1880 bp in the second exon that significantly (P < 0.0001) affected EA activity; this result could be used in breeding programs to improve beer quality. In addition, African accessions had the highest EA activity and TAX content, and the richest germplasm resources were from Asia, indicating the high potential value of Asian barley. CONCLUSION: This study provided insight into understanding the relationship, EA activity, TAX content with the SNPs of HvXYN1 in barley. These SNPs can be applied as DNA markers in breeding programs to improve the quality of barley for beer brewing after further validation. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12870-019-1747-5) contains supplementary material, which is available to authorized users.